Exosomal TRIM3 is a novel marker and therapy target for gastric cancer - Hailong Fu (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background Exosomes are critically involved in cancer development and progression. The exosomal contents have been suggested as ideal cancer biomarkers. In this study, we investigated the expression of exosomal proteins in the serum of gastric cancer patients and their roles in gastric cancer. Methods The proteomic profile of exosomes from the serum of gastric cancer patients was detected by using LC-MS/MS. The expression of TRIM3 in exosomes from the serum of gastric cancer patients and healthy controls was assessed by ELISA and western blot. Immunohistochemistry was used to detect TRIM3 expression in gastric cancer tissues and their matching adjacent tissues. The growth and migration abilities of gastric cancer cells with TRIM3 overexpression or knockdown in vitro were evaluated by colony formation assay and transwell migration assay. The effects of TRIM3 overexpression or knockdown on gastric cancer growth and metastasis in vivo were investigated by using subcutaneous xenograft tumor and peritoneal metastasis mouse model. The effects of TRIM3-overexpressing exosomes on gastric cancer growth and metastasis in vitro and in vivo were also evaluated. Results We found that the expression levels of TRIM3 mRNA and protein were decreased in gastric cancer tissues compared to the matched control tissues. In addition, the levels of TRIM3 protein in the serum exosomes of gastric cancer patients were lower than that in healthy controls. We demonstrated that TRIM3 overexpression reduced while TRIM3 knockdown promoted the growth and metastasis of gastric cancer in vitro and in vivo through the regulation of stem cell factors and EMT regulators. Moreover, exosomes-mediated delivery of TRIM3 protein could suppress gastric cancer growth and metastasis in vitro and in vivo. Conclusions Taken together, our findings suggest that exosomal TRIM3 may serve as a biomarker for gastric cancer diagnosis and the delivery of TRIM3 by exosomes may provide a new avenue for gastric cancer therapy.